Geochemistry of magnetite layers in the upper zone of the Bushveld Complex, South Africa - Maila, Ramphelane Prince (My University, 2015)
The Upper Zone (UZ) of the Bushveld Complex (BC) comprises several magnetitite layers throughout the entire sequence with the most prominent layer, the 2 m thick Main Magnetitite Layer (MML), located towards the base of the sequence. Magnetite mineral separates have been obtained from the UZ with particular focus on the MML in vertical profiles through the MML, Layer 1 and bifurcations of the MML, as well as profiles along the base of the MML and bifurcations. Magnetite mineral separates were also collected from Bierkraal and UCAR mine drill cores. The magnetite mineral separates were analyzed primarily for Cr and V as these two elements have the highest partition coefficients (D>200 and D=20-25 respectively) in magnetite and can be used as magmatic tracers. Electron microprobe data from the Bellevue drill core are also included. The gradational upper contacts of magnetitite layers with overlying anorthosite could be interpreted to suggest that the magnetitite layers accumulated through crystal settling. However, vertical profiles through 1 m of the MML all show an upward exponential decrease in Cr content (12 000-580 ppm) which is inconsistent with crystal settling but better explained by diffusion controlled bottom crystallization. The sharp base of the MML with the underlying anorthosite may suggest that the MML crystallized due to an abrupt event. The MML is not entirely homogeneous as evidenced by lateral heterogeneity along the base of the MML, identified by irregular Cr concentrations along the base of the MML and magnetitite bifurcations. This heterogeneity further supports the contention that the magnetitite layers are a product of diffusion controlled bottom crystallization. Reversals in Cr content, of differing magnitudes, in 3 of 4 vertical profiles above a dome structure interrupting the MML and in 2 of 4 vertical profiles through the MML, are attributed to intermittent convection on various scales bringing primitive undepleted magma into the crystallization zone. The magnitude of the reversals depends on the level to which the convection descends. The feldspar parting, a 10 cm thick horizon with cumulus plagioclase 1 m above the base of the MML, appears at a fairly constant Cr content in magnetite. The lack of a chemical break immediately above the feldspar parting suggests a physical process, such as pressure change, as a mechanism to account for the mineralogical change from the feldspar parting into massive magnetite in the upper portion of the MML. Vanadium, unlike Cr shows no systematic trends. Vanadium content of magnetitite layers is found to be comparable to that of the disseminated magnetite thus ruling out the possibility of a change in fo2 as a mechanism to induce magnetite crystallization. Disseminated magnetite in the UZ is suggested to have re-equilibrated with pyroxene and/or olivine during subsolidus ii cooling resulting in lower MgO contents of the disseminated magnetite compared to that of massive magnetitite layers. Similarities between magnetitite layers in Magnet Heights (eastern lobe); UCAR mine drill core, east of Brits (western lobe); Bierkraal drill core, north of Rustenburg (western lobe) and Bellevue drill core (northern limb) suggest that the different lobes of the BC may be connected.
A Dissertation submitted to the School of Geosciences, University of the Witwatersrand, Johannesburg, South Africa in fulfilment of the requirements for the degree of Master of Science. May 2015
Keywords: Geochemistry.; Magnetite.; Magnetite--South Africa--Bushveld Complex.